Quantum well intermixing using pulsed laser irradiation - Ong, Teik Kooi. (2008)
The objective of this project are to develop and optimize the P-PAID techniques on InGaAs/InGaAsP laser structures using a pulsed Nd:YAG laser, to develop a mathematical model to calculate the band structure in a strain-free interdiffused QW and etc.